2024
DOI: 10.3390/su16030960
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality and Equality in Education Using the European Foundation for Quality Management Excellence Model—A Literature Review

Effrosyni Taraza,
Sofia Anastasiadou,
Christos Papademetriou
et al.

Abstract: Purpose: The purpose of this study was to determine the effects of the European Foundation for Quality Management (EFQM) Excellence Model on education and its contribution to ensuring high-quality education equality. Design/Methodology/Approach: A systematic literature review was conducted based on data from three academic publishers (Taylor & Francis, Emerald, and Elsevier Science Direct). Of the 69 journal articles, 61 were published between 2003 and 2023 and documented the results of the EFQM quality to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 151 publications
1
0
0
Order By: Relevance
“…In contrast, EFQM received less focus within the Chinese context, primarily featuring in theoretical discussions without substantial evidence of its practical application. This finding corresponds to a recent study, which reported that EFQM has yet to be broadly adopted within the educational domain [122]. Despite this, case studies in Europe [13] and Asia [123] have demonstrated the feasibility of EFQM within academic libraries.…”
Section: Rq 2 What Types Of Qm Models Have Been Discussed and Impleme...supporting
confidence: 88%
“…In contrast, EFQM received less focus within the Chinese context, primarily featuring in theoretical discussions without substantial evidence of its practical application. This finding corresponds to a recent study, which reported that EFQM has yet to be broadly adopted within the educational domain [122]. Despite this, case studies in Europe [13] and Asia [123] have demonstrated the feasibility of EFQM within academic libraries.…”
Section: Rq 2 What Types Of Qm Models Have Been Discussed and Impleme...supporting
confidence: 88%